The Effect of the Science Stations Strategy on Developing Biological Concepts and Acquiring Science Operations Skills among Classroom Teacher Students at Al-Isra University - Tannous, Intesar George; Tannous, Firas George; Tannous, Fares George; Al-Dlalah, Moham’d M. (Journal of Ecohumanism, 2024)
This study investigated the effect of using the scientific station's strategy in developing biological concepts and acquiring science operations skills among classroom teacher students at Al-Isra University in Jordan compared to the usual method. The study was applied to a sample of (61) female students from the Department of Class Teacher and Records in Life and Health Sciences. The two classes were randomly assigned to an experimental group of (30) female students and a control group of (31) female students. The researchers used the quasi-experimental approach. To achieve the study objectives, a conceptual test consisting of (25) items was prepared to measure the level of development of biological concepts, as well as a scale comprised of (20) items was ready to measure the level of acquisition of science operations skills among the study members. The psychometric properties of the study tools were verified, and the results showed a statistically significant effect at the significance level (α=05.0) for the strategy of scientific stations in developing biological concepts and acquiring science operations skills for the benefit of the experimental group.